2020
DOI: 10.1186/s13046-020-01766-w
|View full text |Cite
|
Sign up to set email alerts
|

Roquin1 inhibits the proliferation of breast cancer cells by inducing G1/S cell cycle arrest via selectively destabilizing the mRNAs of cell cycle–promoting genes

Abstract: Background Dysregulation of cell cycle progression is a common feature of human cancer cells; however, its mechanism remains unclear. This study aims to clarify the role and the underlying mechanisms of Roquin1 in cell cycle arrest in breast cancer. Methods Public cancer databases were analyzed to identify the expression pattern of Roquin1 in human breast cancers and its association with patient survival. Quantitative real-time PCR and Western blots were performed to detect the expression of Roquin1 in breast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Roquin1/2 has been shown to play an important role in suppressing autoinflammation by enhancing the mRNA decay of proinflammatory cytokines 31 . In our previous study, we found that Roquin1 was able to suppress breast tumor progression by inducing cell cycle arrest of breast cancer cells 32 . However, there are very few reports on the role of Roquin2 in tumor progression 26 , 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Roquin1/2 has been shown to play an important role in suppressing autoinflammation by enhancing the mRNA decay of proinflammatory cytokines 31 . In our previous study, we found that Roquin1 was able to suppress breast tumor progression by inducing cell cycle arrest of breast cancer cells 32 . However, there are very few reports on the role of Roquin2 in tumor progression 26 , 27 .…”
Section: Discussionmentioning
confidence: 97%
“…RIP experiment was conducted as previously described 33 . The protein‐RNA complexes were immunoprecipitated by protein A/G beads, and total RNA extracted with TRIzol, followed by detection with RT‐PCR.…”
Section: Methodsmentioning
confidence: 99%
“…ATR can phosphorylate proteins involved in DNA replication, DNA recombination and repair, and cell cycle regulation in response to DNA damage ( Snedeker et al, 2017 ). Due to its extensive role in DDR, ATR inhibition has great potential in cancer treatment ( Cheng et al, 2017 ; Jin et al, 2021 ; Lu et al, 2020 ). Therefore, suppressing ATR signal transduction by inhibitors may exert antitumor effects against ESCC ( Gorecki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%